2010
DOI: 10.1007/s12070-010-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

A survey of ear, nose and throat disorders in rural India

Abstract: In this survey 4.31% of the rural population of the district were having ENT ailments. The highest numbers rural population (35.65%) were having ear diseases. This was primarily due to low socioeconomic status and lack of awareness of the population. The nasal problem was seen in 23.57%, while throat problem was seen in 16.58%. The percentage of head neck malignancy in this survey was 0.0028.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 5 publications
1
28
0
2
Order By: Relevance
“…For Nigeria, the prevalence of diseases of ear, nose and throat were 62.7%, 23.0% and 9.6%, respectively [7]. In Senegal, the rates were 22.8%, 54.6% and 22.4% [8] and in India, the rates were 36.6%, 23.5% and 16.58% respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…For Nigeria, the prevalence of diseases of ear, nose and throat were 62.7%, 23.0% and 9.6%, respectively [7]. In Senegal, the rates were 22.8%, 54.6% and 22.4% [8] and in India, the rates were 36.6%, 23.5% and 16.58% respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…It may be further broken down into non-cholesteatomatous chronic otitis media (NCCOM) and cholesteatomatous chronic otitis media (CCOM) according to the absence or presence of a cholesteatoma [1]. Non-cholesteatomatous chronic otitis media (NCCOM) is very common condition in India [2], with resultant persistent and broad tympanic membrane perforations. The major symptom these patients present is intermittent otorrhea, usually associated to upper airway infections or a past history of extrinsic contamination (swimming in pools or ocean).…”
Section: Introductionmentioning
confidence: 99%
“…The otorrhea is typically painless, without giving off foul smell, together with hearing loss. By doing otoscopy one commonly finds a perforation in the pars tensa of the tympanic membrane of varied size and shape, the middle ear mucosa has an almost normal appearance, except for some degrees of hyperemia [2].…”
Section: Introductionmentioning
confidence: 99%
“…These approaches show promise in other low-income countries, but require the availability of precise equipment and trained audiologists, which remains a challenge in many low-income schools and school districts. Similarly, studies of hearing impairment prevalence found that Nigeria (Fasunla, Samdi, & Nwaorgu, 2013), Kenya (Hatcher et al, 1995), and India (Singh & Kumar, 2010) all relied on clinic, hospital, or health center personnel to conduct the screenings.…”
Section: Hearing Screeningmentioning
confidence: 99%